2021
DOI: 10.7717/peerj.11446
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids from inflorescences fractions of Trema orientalis (L.) Blume (Cannabaceae) against human pathogenic bacteria

Abstract: Background Cannabinoids; tetrahydrocannabinol (THC), cannabidiol (CBD) and cannabinol (CBN), might show antibacterial activity. Trema orientalis is a species in the Cannabaceae that is closely related to Cannabis through plastome phylogenetic evidence. This species is widely distributed throughout tropical Asia and is used as traditional medicine, particularly for the treatment of infectious diseases. However, no studies on the antibacterial activity of cannabinoid-containing inflorescences extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Given that the progenitor of the cannabinoid synthases is found in the related genera Humulus, Parasponia and Trema , it is reasonable to ask whether these enzymes actually make cannabinoids. In fact, it has recently been found that THCA, CBDA and cannabinol (CBN) are present in inflorescences of Trema orientalis (Napiroon et al, 2021). Looking at the active site residue alignment in Figure 6 the Trema sequence, which is about 60% identical to the Cannabis cannabinoid synthase sequences shows about the same percentage identity in the active site.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the progenitor of the cannabinoid synthases is found in the related genera Humulus, Parasponia and Trema , it is reasonable to ask whether these enzymes actually make cannabinoids. In fact, it has recently been found that THCA, CBDA and cannabinol (CBN) are present in inflorescences of Trema orientalis (Napiroon et al, 2021). Looking at the active site residue alignment in Figure 6 the Trema sequence, which is about 60% identical to the Cannabis cannabinoid synthase sequences shows about the same percentage identity in the active site.…”
Section: Discussionmentioning
confidence: 99%
“…GC-based analytical techniques have been used routinely in the analysis of phytocannabinoids in plant samples (Table 1), particularly in been reported from Avicennia marina, 31 Trema orientalis, 60 and phytoplankton. 59 Both GC-FID and GC-MS, including GC-MS/MS, are extensively used in phytocannabinoids analysis from plant extracts (Table 1).…”
Section: Gc Analysis Of Phytocannabinoids In Plant Samplesmentioning
confidence: 99%
“…Several papers have been published on the GC-MS or GC-MS/MS analysis of phytocannabinoids from plant matrices. 32,[34][35][36]38,41,[43][44][45][46][47][48][49][50][51][52][53][54][55][56]59,60 Dried flowering tops of C. sativa, after hydrodistillation, were extracted with acidic n-hexane using a standard maceration technique at room temperature involving constant agitation in the dark for 3 h, and the GC-MS analysis of the resulting extract afforded identification of CBD (3). 32 The presence of other phytocannabinoids in the extract, for example, CBDV (12), CBDVA (14), THC (10), THCV (13), and THCVA (15), was determined by LC-MS/MS analysis.…”
Section: Gc Analysis Of Phytocannabinoids In Plant Samplesmentioning
confidence: 99%
“…Briefly, it should be noted that there are non- C. sativa plants among the Cannabaceae family that are, or have been, used medicinally around the world but have received only minor attention from the scientific community [ 56 ]. For example, extracts of flower heads of Trema orientalis , which is widely distributed in tropical regions of Asia, have been reported to exhibit antibacterial activities against methicillin-resistant S. aureus (ATCC 43300), P. aeruginosa (ATCC 27853), and Acinetobacter baumannii (ATCC 19606) with MICs of 64–125 µg/mL, 31–64 µg/mL and 31–64 µg/mL, respectively [ 56 ]. Such extracts were shown to contain THC, CBN and, to a lesser extent, CBD.…”
Section: The Antimicrobial Properties Of Cannabis and Cannabis-derive...mentioning
confidence: 99%